Cares in the Age of Communication: Health Education and Healthy Lifestyles - Herrera-Peco, Iván; de la Torre-Montero, Julio C. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Nowadays, the power of internet and social media to share information and connect with others is a reality that has also changed the way people communicate about health information, but also to create and share health information with others. The loss of confidence in health professionals could be dangerous with regard to the diffusion of information about community health and possible alterations of procedures and systems designed to maintain and improve it. So, this situation about the Spreading health education through Social Media requires research and the design of new ways to approach social media users, especially, young people. Initiatives where health professionals must be the main actors and drive the communication initiatives focused on community health with the main goal of recovery the people confidence when they in health issues. Health education has an important challenge in front of all healthcare providers in multiple aspects of caring. Patients and people concerns about self-cares must be addressed and every one of us is an agent for change. This Special Issue collects 11 research studies focused to the promotion of health and healthy lifestyles through adequate communication strategies.